IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS III DI SDN 066055 MEDAN DENAI: Penelitian Tindakan Kelas - Adelia Syahputri; Ambar Wulan Sari; Hotnida Simarmata (STKIP Subang, 2024)
Culturally Responsive Teaching (CRT) is a theoretical approach aimed at helping students embrace and strengthen their cultural identities while enhancing academic performance. The purpose of this article is to describe the application of the Culturally Responsive Teaching (CRT) approach in teaching Indonesian at SD Negeri 066055 Medan Denai. The Culturally Responsive Teaching (CRT) approach has become a primary focus in educational literature to enhance the quality of teaching that values the cultural diversity of students. This research is Classroom Action Research (CAR) that refers to planning, action, observation and evaluation, and reflection. This research was conducted in 2 cycles, with each cycle consisting of 2 meetings. This research was conducted at SD Negeri 066055 Medan Denai, with the subjects of the study being third-grade students, totaling 19 children. The data collection techniques used are tests, documentation, and observation. The analysis used in this study is quantitative analysis with the use of LKPD (Student Worksheet). The results of the analysis in cycle I showed a completeness of 42% (19 students), and in cycle II it was 84%. (19 peserta didik).Thus, it can be concluded that the Culturally Responsive Teaching (CRT) approach can be implemented in Grade III of State Elementary School 066055 Medan Denai.